Operando Photoelectron Spectroscopy Analysis of Li6PS5Cl Electrochemical Decomposition Reactions in Solid-State Batteries - Aktekin, Burak; Kataev, Elmar; Riegger, Luise M.; Garcia-Diez, Raul; Chalkley, Zora; Becker, Juri; Wilks, Regan G.; Henss, Anja; Bär, Marcus; Janek, Jürgen (ACS Energy Letters, 2024)
It is crucial to understand at which potentials electrolyte decomposition reactions start and which chemical species are present in the subsequently formed decomposition films, e.g., solid electrolyte interphase (SEI). Herein, a new operando experimental approach is introduced to investigate such reactions by employing hard X-ray photoelectron spectroscopy (HAXPES). This approach enables the examination of the SEI formed below a thin metal film (e.g., 6 nm nickel) acting as the working electrode in an electrochemical cell with sulfide-based Li6PS5Cl solid electrolyte. Electrolyte reduction reactions already started at 1.75 V (vs Li+/Li) and resulted in considerable Li2S formation, particularly in the voltage range 1.5-1.0 V. A heterogeneous/layered microstructure of the SEI is observed (e.g., preferential Li2O and Li2S deposits near the current collector). The reversibility of side reactions is also observed, as Li2O and Li2S decompose in the 2-4 V potential window, generating oxidized sulfur species, sulfites, and sulfates.
CRIS-Team Scopus Importer:2024-07-19